Exploring the Relationships Between Hemodynamic Stresses in the Carotid Arteries - Ziegler, Magnus; Alfraeus, Jesper; Good, Elin; Engvall, Jan; de Muinck, Ebo; Dyverfeldt, Petter (Frontiers in Cardiovascular Medicine, 2021)
Background:Atherosclerosis manifests as a focal disease, often affecting areas with complex hemodynamics such as the carotid bifurcation.The magnitude and regularity of the hemodynamic shear stresses acting on the vessel wall are thought to generate risk patterns unique to each patient and play a role in the pathogenesis of atherosclerosis.The involvement of different expressions of shear stress in the pathogenesis of carotid atherosclerosis highlights the need to characterize and compare the differential impact of the various expressions of shear stress in the atherosclerotic carotid bifurcation.Therefore,the aim of this study is to characterize and compare hemodynamic wall shear stresses(WSS) in the carotid arteries(CA) of subjects with asymptomatic atherosclerotic plaques.WSS were also compared against vessel diameter and bifurcation angle to examine the relationships with the geometry of the carotid bifurcation. Methods:4D Flow MRI and contrast-enhanced MRA data were acquired for 245 subjects with atherosclerotic plaques of at least 2.7mm in conjunction with the Swedish CArdioPulmonary bioImage Study(SCAPIS).Following automatic segmentation and geometric analysis,time-resolved WSS and near-wall turbulent kinetic energy(nwTKE) were derived from the 4D Flow data.Whole-cycle parameters including time-averaged WSS and nwTKE,and the oscillatory shear index(OSI) were calculated.Pairwise Spearman rank-correlation analyses were used to investigate relationships among the hemodynamic and geometric parameters. Results:179 subjects were successfully segmented using automated tools and subsequently geometric and hemodynamic analyses were performed.Temporally-resolved WSS and nwTKE were strongly correlated,rho=0.64.Cycle-averaged WSS and nwTKE were moderately correlated, rho=0.57.Cycle-average nwTKE was weakly correlated to OSI(rho=-0.273), revealing that nwTKE provides information about disturbed flow on the vessel wall that OSI does not.In this cohort, there was large inter-individual variation for both WSS and nwTKE.Both WSS and nwTKE varied most within the external CA.WSS, nwTKE, and OSI were weakly correlated to vessel diameter and bifurcation angle. Conclusion:The turbulent and mean component of WSS were examined together in vivo for the first time, and a strong correlation was found between them.nwTKE presents the opportunity to quantify turbulent WSS in vivo and gain insight into the effects of disturbed flow on the vessel wall.Neither vessel diameter nor bifurcation angle were found to be strongly correlated to the turbulent or mean component of WSS in this cohort.